Corporate Social Responsibility and Cheating Behavior: The Mediating Effects of Organizational Identification and Perceived Supervisor Moral Decoupling - Luan, Kun; Lv, Mengna; Zheng, Haidong (Frontiers in Psychology, 2022)
Previous corporate social responsibility (CSR) studies at the employee level have focused on the influence of CSR on employees’ positive attitudes and behavior. However, little attention has been paid to the relationship between CSR and unethical behavior and the underlying mechanism. Based on social information processing theory, this study investigates how CSR affects employee cheating via employees’ organizational identification and perceived supervisor moral decoupling. Additionally, this study discusses the moderating effect of employee bottom-line mentality on these relationships. We test this two-path model using a sample of MBA students in China. The results indicate that both organizational identification and perceived supervisor moral decoupling mediate the relationship between CSR and cheating, and employee bottom-line mentality moderates the effect of CSR on perceived supervisor moral decoupling. Specifically, for employees low in bottom-line mentality, CSR has a significantly negative impact on perceived supervisor moral decoupling, but the same relationship is insignificant for employees with a strong bottom-line mentality. Overall, our results uncover the relationship between CSR and employee cheating and extend the understanding of the influence of CSR on employees.